EFFORTS TO OVERCOME- DIS-HARMONIZATION OF REGIONAL REGULATIONS TO REALIZE HARMONIOUS REGIONAL REGULATION - Nasir, Citra; Attas, Nasrah Hasmiati; Saputra, Tri Eka; Susanto, Cristofer (IJBLE Scientific Publications Community Inc., 2022)
Every law formed should be consistentand harmonious with other laws and regulations, but it does not rule out possibility that laws and regulations turn out to be contrary to higher and / or equivalent law and regulation. For example, at the regional level, it is often found that the substance of local regulations is considered problematic so that it must be canceled or revised, so that strategic steps are neededin order to overcome this. Thisresearch aims to determine efforts to overcome disharmonization of regional regulations. The type of researchused is a normative legal research method with a statutory approach (statute approach) and a conceptual approach (conceptual approach), which is further analyzed deductively. The results of the research are an effort to overcome the disharmonization of regional regulations through preventive supervision in the formation carried out by the central government before local regulations are ratified and promulgated, in the form of facilitation and evaluation to ensure the formation of regional regulations has met good regional regulations. In the meantime, strict oversight is conducted on local regulations that have been enacted and hold legal authority. These regulations are subject to two types of supervision: internal supervision, which involves providing clarifications without the power to cancel but only making recommendations; and external supervision, which is carried out by the Supreme Court to annul the Bylaw.